Ankle tendon electrical stimulation to enhance sensation of walking on a slope in walking-in-place - Ota, Takashi; Matsumoto, Keigo; Aoyama, Kazuma; Amemiya, Tomohiro; Narumi, Takuji; Kuzuoka, Hideaki (Frontiers in Virtual Reality, 2024)
This study aimed to develop an effective VR locomotion technique for walking through virtual environments with sloped ground. Thus, this paper presents a novel method for inducing the sensation of walking on a slope in walking-in-place (WIP) using ankle tendon electrical stimulation (TES), which induces the body tilt sensation. We conducted two experiments to evaluate the effectiveness of the proposed method. In Experiment 1, we evaluated the sensation of ascending and descending slopes induced by the proposed method in a setup where electricity flows when the feet are grounded by comparing it to the sensation on a real slope. Experiment 1 demonstrated a marginally significant effect of electrical stimulation on the sensation of ascending or descending slopes. We attributed this to the short duration of ankle TES and the influence of the user's interpretation of the ankle TES. Based on the findings, Experiment 2 was conducted in a setup where ankle TES was constantly applied. The results indicated that participants who focused on the subjective body tilt sensation elicited by TES and those unaware of the TES effect experienced an ascending sensation with an anterior ankle TES and a descending sensation with a posterior ankle TES. Conversely, those who focused on the tactile or force sensation induced by ankle TES experienced the opposite effect. Based on this finding, we have constructed an implementation guide for a WIP system that incorporates ankle TES to present the desired sensation of ascending or descending slopes in virtual environments.